Identifying Indonesian Consumer Buying Behavior to Design Gundam Model KITS Marketing Strategy - Zaputra, Zetra Iez; Iskandar, Budi Permadi (Journal of Business and Management, 2013)
Nowadays, people in Indonesia can have hobbies and collect things that are produced overseas. With the introduction of television, satellite, and especially internet, it is easy to find information about things they want to collect. And one of the most popular model kit collected by Indonesian people is Gundam plastic model kit that produced in Japan. Mobile Suit Gundam is a metaseries created by Sunrise that first aired in 1979 and until now the series already released in numerous media like TV series, OVAÃ¢â‚¬â„¢s, manga, photo novels, and video games. Gundam plastic model kit is plastic model that depicting the mechanical robots, vehicles, and characters from the Mobile Suit Gundam series. The model kits consist of some line-up, they are Super Deformed, High Grade, Master Grade, Perfect Grade, Real Grade, and Mega Size Model. The objective of this research is to measure Indonesian Gundam Otaku buying behavior and Gundam Plastic Model market condition, so marketers could identify and develop marketing strategy to maximize the opportunity that existing in people who collect Gundam Plastic Model. This study concludes two stages, the qualitative study and the quantitative study. The qualitative study used for determining the condition and the problem identification. The quantitative study includes the questionnaire and the analysis. The target population in this study is Indonesian people who collect Gundam Model Kit. Respondents are Indonesian people that collecting Gundam Model kit from different backgrounds. The number of sample for this research is 250. Descriptive analysis, frequency analysis, and cross tabulation were used to analyze the data. The findings including how Indonesian Gundam Model Kit collectors know the product for the first time, the favorited line-up, how much they spend for their collection, how they usually buy their collection, which friend that affect them in collecting the model kit, and decision factors that affect them in collecting Gundam Model Kit.Ã‚Â Keywords: Consumer Behaviors, Consumer Preferences, Buying Decision Factors, AISAS, 4P Marketing Mix